2016
DOI: 10.1037/prj0000222
|View full text |Cite
|
Sign up to set email alerts
|

The peer support workforce: Results of a national survey.

Abstract: Results of this survey provide critical information about the job characteristics of peer specialists and data that should be informative for mental health authorities as they address the needs of this workforce. However, our findings also suggest that ambiguity remains regarding the roles, tasks, and training of peer specialists, which could benefit from further study that would help to clarify the unique role of these professionals within the mental health arena. (PsycINFO Database Record

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
116
4
10

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 129 publications
(138 citation statements)
references
References 17 publications
8
116
4
10
Order By: Relevance
“…Contrary to the USA studies (Cronise et al, ; Salzer et al, ) indicating that most PSSs work in community settings, three‐quarters of the participants in our study reported working in inpatient settings. This could be due to the strong focus on inpatient services in the mental health field in Switzerland, in comparison with other countries, where the community sector is more developed (Hewlett & Moran, ).…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Contrary to the USA studies (Cronise et al, ; Salzer et al, ) indicating that most PSSs work in community settings, three‐quarters of the participants in our study reported working in inpatient settings. This could be due to the strong focus on inpatient services in the mental health field in Switzerland, in comparison with other countries, where the community sector is more developed (Hewlett & Moran, ).…”
Section: Discussioncontrasting
confidence: 99%
“…Based on the results of our survey, salaries seem to be higher in Switzerland than in the United States (Cronise et al, ) (29‐38 CHF vs 15 USD per hour). The currency conversion rate between the CHF and the USD is nearly one‐to‐one, and the annual median of equalized disposable incomes is comparable between the two countries (Organisation for Economic Cooperation & Development, ).…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…For example, Chinman et al are developing a peer specialist fidelity measure for two content areas: services provided by peer specialists and factors that support or hamper the performance of those services. Cronise et al conducted a US national survey to identify the roles, tasks, settings, job training and compensation currently offered to those with the title of “peer specialist”. They found that peers are no longer just part‐time workers in community based settings.…”
mentioning
confidence: 99%